Adaptive Algorithm for Optimal Route Configuration in Multi-Hop Wireless Sensor Network - Shabani, Hikma; Ahmed Mohamed, Ahmed Haidar; Norhuzaimin, Julai; Musse, Mohamud Ahmed; Hoole, P.R.P.; Marai, Majdi (International Science Press, 2017)
Wireless Sensor Networks (WSNs) are best solutions for numerous aspects of engineering applications such as monitoring, control and surveillance of electrical plant amongst others. Autonomously, sensors will communicate with each other, collaborate, share and forward information in a multi-hop fashion without any centralized controller. To gather relevant data, the route optimization mechanism is used to solve the long routing problem and provide the shortest path amongst communicating nodes. Thus, this shortest path criterion is not suitable for WSN as it may lead to power drainage of several nodes and may cause high signaling and processing costs due to the network reconstruction. This paper proposes an optimal route configuration technique based on an adaptive genetic algorithm in which the architecture of multi-hop wireless sensor network is considered as a distributed computing infrastructure. The obtained results show that the proposed algorithm provides an optimal route configuration with the best performance in terms of evaluating the covered distance, packet loss and time delay.